Use of lexical items in job interviews by recent graduates in Malaysia. Issue 4 (5th November 2020) - Amutan Krishnan, Isai; Mohd Jan, Jariah; Zainuddin, Siti Zaidah Binti
Abstract : Purpose: The purpose of this paper is to explore the knowledge of lexical items in a job interview by recent graduates. Design/methodology/approach: The data were collected from one of the organisations in the Klang Valley, Malaysia. Twenty-seven recent graduates participated in the study. The structured standard interview questions were used to elicit the job interview data. The data were recorded and analysed qualitatively by using Allwood's (1999a, b, c) communicative behaviour theory. Findings: The findings showed that the lexical items used by the interviewees varied and revealed their knowledge of lexical items in relation to these five characteristics: personality, skills, capability, experience and self-motivation. The successful interviewees reflected their knowledge of lexical items that indicated their confidence in in the job interviews. The lexical items used by the reserved interviewees were limited that displayed their personalities and reflected uncertainty and lack of confidence. The unsuccessful interviewees used limited lexical items and were vague and evasive in answering questions. This could also be not convincing enough to influence the outcome of the interviews positively. Practical implications: The findings of this study can assist policymakers such as officials of higher learning institutions to integrate interview workshops and mock interviews into their current curriculum as a form of preparation for undergraduates. These mock interviews can be more appropriate if experienced interviewers are utilised from the outsourcing organisations. Social implications: It creates an awareness for job applicants especially undergraduates after completing their studies that knowledge of lexical items are important in job interviews. Originality/value: The use of appropriate lexical items play an important role in job interviews as they have shown that all the successful interviewees had used them to good effect in their interactions with the interviewer.